Plasma nitriding of surface Mo-Enriched sintered iron - Bendo, T. (2021)
Plain iron samples produced by powder metallurgy were submitted to a single thermal cycle involving plasma-assisted sintering and simultaneous surface alloying with Mo followed by nitriding using a plasma reactor. The microstructural characterization of the samples was carried out by optical and scanning electron microscopy in addition to X-ray diffraction. Microhardness tests were also performed. EDX line profiles of the concentration of Mo from the surface to the bulk of the sintered samples showed that the alloying element diffused down to depths of about 25 μm under the sintering conditions applied. A significant increase in microhardness was observed for samples enriched with Mo and subsequently nitrided. This behavior was attributed to the precipitation of nitrides and the presence of Mo in solid solution